Solitary Fibrous Tumor of the Orbit: CT and MR Imaging Findings - Kim, H.J; Kim, H.-J.; Kim, Y.-D.; Yim, Y.J.; Kim, S.T.; Jeon, P.; Kim, K.H.; Byun, H.S.; Song, H.J. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE:Solitary fibrous tumor (SFT) is a rare spindle-cell neoplasm originating from mesenchymal fibroblast-like cells. The purpose of this study was to describe the CT and MR imaging features of SFTs in the orbit.MATERIALS AND METHODS:We retrospectively reviewed CT and MR images in 6 patients (2 men and 4 women), aged 18 to 51 years, with SFT proved on histologic examination located in and around the orbit. All patients underwent CT (including dual-phase CT in 3), and MR imaging was obtained in 3. We evaluated the imaging findings with emphasis on the location, size, margin, internal architecture, and pattern of enhancement of the lesion.RESULTS:All 6 lesions were found as a solitary, well-defined mass, ranging in size from 18 to 30 mm (mean, 24 mm). Three were located in the postseptal orbit, 2 in the lacrimal sac, and 1 on the lower eyelid. Compared with the cerebral cortex, all 3 lesions examined by MR imaging showed homogeneous isointense signal intensity on T1-weighted images and heterogeneous mixed isointense and hyperintense signal intensity on T2-weighted images. On visual inspection, all 6 lesions showed marked homogeneous (n = 4) or heterogeneous (n = 2) enhancement on postcontrast CT and MR images. In 3 patients examined with dual-phase CT, all lesions demonstrated rapid enhancement with early washout of contrast material.CONCLUSION:SFT might be included in the differential diagnosis of soft tissue masses in the orbit, if one sees a markedly enhancing mass showing the similar characteristics to those of the internal carotid artery on postcontrast CT or MR images.